Continuous separation of blood cells in spiral microfluidic devices - Nivedita, Nivedita; Papautsky, Ian (Biomicrofluidics, 2013)
Blood cell sorting is critical to sample preparation for both clinical diagnosis and therapeutic research. The spiral inertial microfluidic devices can achieve label-free, continuous separation of cell mixtures with high throughput and efficiency. The devices utilize hydrodynamic forces acting on cells within laminar flow, coupled with rotational Dean drag due to curvilinear microchannel geometry. Here, we report on optimized Archimedean spiral devices to achieve cell separation in less than 8 cm of downstream focusing length. These improved devices are small in size (<1 in.2), exhibit high separation efficiency (∼95%), and high throughput with rates up to 1 × 106 cells per minute. These device concepts offer a path towards possible development of a lab-on-chip for point-of-care blood analysis with high efficiency, low cost, and reduced analysis time.